Psychological distress as predictor of quality of life in men experiencing infertility: a cross-sectional survey - Knauth Daniela R; Fleck Marcelo MP; Cordova Fernanda P; Ezer Hélène; Chachamovich Eduardo; Chachamovich Juliana LR; Passos Eduardo P (BMC, 2010)
Abstract Background Infertility is associated with impairment in human life. The quality of life (QOL) construct allows measuring the impact of health conditions in a broader way. The study aimed to explore the impact of the psychological distress on QOL's dimensions in men experiencing infertility. Methods 162 men were completed a socio-demographic form, SF-36, WHOQOL-BREF, Beck Anxiety Inventory and Beck Depression Inventory. Hierarchical regressions included demographic and clinic variables, and subsequently depression and anxiety were added. Results and Discussion Model 1 was not accurate in predicting QOL. R2 values ranged from 0.029 (Social Functioning) to 0.149 (Mental Health). Eight domains were not associated with any of the predictors. In the second model, a R2increase was observed in all domains. R2 of QOL scores ranged from .209 (Role Physical) to .406 (Social Functioning). The intensity of the depression was a significant predictor for all outcomes. The load of depression was higher than the ones of the socio-demographic and clinical variables. Anxiety levels have also presented the same effect, but with less intensity. Conclusion Subthreshold depression and anxiety were major predictors of QOL in men experiencing infertility. Health professionals need to include assessment of psychological symptomatology to plan more efficient interventions to infertile patients.